The use of irradiation as pre-treatment for the production of bagoong isda - Ambas, Maria Edlyn Tolentino
ABSTRACT Two species of fish, galunggong and dilis, were subjected to irradiation prior to production of bagoong isda. Radiation doses used were 3 and 10 kGy. Fish:salt ratio was 3:1 and fermentation was done for 45 days at room temperature. Effect of radiation on physico-chemical, microbiological and sensory qualities of the bagoong isda was determined. Pre-treating of fish with radiation resulted in a significant increase in the protein content for the galunggong sample. However, protein content of dilis sample did not vary significantly. Hydrogen ion concentration for both species were not significantly different. Microbial counts were low but no trend was observed for both bagoong isda samples. Acceptability scores show a significant difference for galunggong samples irradiated at 10 kGy. Based on the results of the study, samples irradiated at 3 kGy gave the highest quality for bagoong isda (galunggong). Bagoong isda (dilis) irradiated at varying doses, on the other hand, showed no difference on all parameters tested.